Schumpeter and Steindl on growth and the transformation to maturity in capitalism - Bloch, Harry; Finch, J. (History of Economic Thought Society of Australia, 2008)
Joseph Schumpeter and Josef Steindl provide distinctive contributions to the analysis of growth and development under capitalism. They each analyse the evolution of competition and use this analysis to determine the growth prospects of mature capitalism. Both reach pessimistic conclusions, although for different reasons. This paper critically examines the analysis of each author and makes suggestions for building on their work to provide a richer theory of economic growth and transformation within advanced capitalist economies.